2015
DOI: 10.1142/s0192415x15500111
|View full text |Cite
|
Sign up to set email alerts
|

Scutellariae radixInduces Apoptosis in Chemoresistant SCC-25 Human Tongue Squamous Carcinoma Cells

Abstract: Scutellariae radix is one of the most widely used anticancer herbal medicines in several Asian countries, including Korea, Japan, and China. Squamous cell carcinoma (SCC) is one of the most common head and neck carcinomas, which is highly invasive and metastatic, and can potentially develop chemoresistance. Therefore, new effective treatment methods are urgently needed. We determined the effects of Scutellariae radix on SCC-25 cells using the WST-1 assay, F-actin staining, flow cytometry analysis, immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…53,54 Significantly, Magnolia officinalis and Scutellaria baicalensis were reported to induce apoptosis both in esophageal and H&N cancers, which could contribute to clinical anticancer effects. 22,23,55,56 The biological anticancer activities and possible mechanisms of the most common single herbs are illustrated in Supplementary Table 3. 22,23,34,54-66…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…53,54 Significantly, Magnolia officinalis and Scutellaria baicalensis were reported to induce apoptosis both in esophageal and H&N cancers, which could contribute to clinical anticancer effects. 22,23,55,56 The biological anticancer activities and possible mechanisms of the most common single herbs are illustrated in Supplementary Table 3. 22,23,34,54-66…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Significantly, Magnolia officinalis and Scutellaria baicalensis were reported to induce apoptosis both in esophageal and H&N cancers, which could contribute to clinical anticancer effects. 22,23,55,56 The biological anticancer activities and possible mechanisms of the most common single herbs are illustrated in Supplementary Table 3. 22,23,34,[54][55][56][57][58][59][60][61][62][63][64][65][66] The data used for the present study were extracted from the NHIRD; however, there inevitably exist some limitations and flaws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scutellariae Radix (SR) is the root of plant Scutellaria baicalensis Georgi (Lamiaceae). SR is a well-known anti-inflammatory and anticarcinogenic herbal medicine [ 10 , 11 ], which can prevent and treat liver injuries caused by hepatitis and liver cancer. SR has certain components, such as baicalin and baicalein, which show an evident antitumor effect on hepatocarcinoma [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The root of S. baicalensis , Scutellariae Radix, has been used worldwide in traditional medicine for the treatment of various human diseases (Boyle et al, 2011[3]). Previous studies have indicated that the extracts of S. baicalensis and its biogenic active ingredients have various pharmacological properties, including antibacterial (Chung et al, 2014[13]), antioxidant (Lin et al, 2014[30]; Chang et al, 2016[7]), anti-tumor (Choi et al, 2015[9], 2016[11]), anti-obesity (Song et al, 2013[42]), anti-asthmatic (Ko et al, 2014[26]; Zhou et al, 2016[47]), anti-hypotensive (Huang et al, 2005[18]; Deng et al, 2012[15]), neuroprotective (Shang et al, 2013[41]; Moon and Park, 2015[33]), and anti-inflammatory activities (Ku and Bae, 2015[27]; Seok et al, 2016[40]). We have recently demonstrated that the protective effects of baicalein, an active component of S. baicalensis , against oxidative stress-induced damage through activation of Nrf2 signaling pathway (Choi et al, 2016[10]).…”
Section: Introductionmentioning
confidence: 99%